(untitled) (Journal of Contemporary Philology, 2022)
The purpose of the present study is to get a better understanding of the reflection process of pre-service EFL teachers at the Faculty of Philosophy in Niš during their theoretical TEFL Methodology course, before entering the EFL classroom. An important element of students’ individual work in this course is their portfolio which consists of the students’ views and opinions on the most important principles of TEFL, recorded at the beginning and the end of the 12-week course, as well as a reflective essay on how and why their beliefs have changed during the course. This qualitative case study employs an in-depth content analysis of these reflective portfolios collected in 2020 and 2021, aiming to identify the themes pertaining to the participants’ emerging teacher identities as well as examine changes in their beliefs about various aspects of language teaching and their own professional development. The findings suggest that reflective thinking should be an essential component of pre-service teacher education courses from the very beginning, and not only during the teaching practice.